Parnaparin: confronto con le altre eparine a basso peso molecolare - Pradelli, Lorenzo; Eandi, Mario (Farmeconomia. Health economics and therapeutic pathways, 2004)
Sodium parnaparin is a low molecular weight heparin (LMWH). The introduction of this drug class has represented a medical advancement in the prevention and therapy of thromboembolic pathologies, as they maintain the same efficacy of unfractionated heparin, but with simplified dosing regimens and reduced side effects. Parnaparin has demonstrated its thromboprophylactic efficacy on both high- and moderate risk surgical patients, besides resulting effective in treating established deep vein thromboses and thrombosis-associated phlebopathies. Alongside these clinical advantages, parnaparin and other LMWHs allow outpatient or home-based therapy of a large number of subjects that should otherwise be treated in hospital, with important savings of health resources and enhanced quality of life for the patients. In Italy, parnaparin drug acquisition cost is the lowest among all LMWHs for the majority of their applications, permitting marginal savings in health costs at the same efficacy level. In summary, the use of parnaparin in thrombotic pathologies has very good efficacy and safety profiles, and has positive clinical and economical outcomes for patients, health system and society as a whole.